CLONING AND EXPRESSION OF THE HUMAN PROTEIN KINASE R GENE, HSPKR, IN BACTERIAL CELLS AND PURIFICATION OF RECOMBINANT HSPKR PROTEIN - Zhigailov , A.V.; Kislitsin , V.Y.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2016)
In eukaryotic cells, phosphorylation of the alpha subunit of eukaryotic translation initiation factor 2 (eIF2α), including by protein kinase R (PKR), is a basic mechanisms of protein synthesis inhibition under various stress conditions. Such phosphorylation inhibits the conversion of GDP to GTP on peIF2α, which is catalysed by eIF2B, causing rapid suppression of mRNA translation initiation. In plants, there is no biochemical or genetic equivalent of eIF2B and the mechanism of mRNA translation regulation via phosphorylation of eIF2α in plant molecular biology remains unclear. Since there is no PKR equivalent in plants, we evaluated the use of heterologous mammalian mPKR, which is activated by double-stranded (ds)RNA, as a tool for controlled phosphorylation of eIF2α in plant systems in vitro and in vivo. In this study, a cDNA encoding human dsRNA-activated PKR (HsPKR) was cloned into the pET23c vector. The gene was expressed in Escherichia coli cells, and recombinant HsPKR protein isolated by immobilised metal ion affinity chromatography (IMAC). The activity of HsPKR in an in vitro plant system was confirmed by evaluation of its ability to phosphorylate wheat TaeIF2α in the presence of [γ-33P]ATP, as well as by immunoblotting using antibodies against phosphorylated eIF2α. Active HsPKR may be useful for in vitro experiments to study molecular mechanisms of mRNA translation regulation in plants through peIF2α phosphorylation, while, HsPKR cDNA has potential for use in production of transgenic plants resistant to viruses.